(untitled) (Research, Society and Development, 2022)
The use of green manures increases the efficiency of soil cover, contributing to better infiltration, moisture, soil microorganisms, and nutrient cycling. The objective of this work was to evaluate the amounts of nutrients released by seven species of green manures in four collection times. The experimental design adopted was the DIC, with 4 evaluation times and three replications. The experiment was carried out at UEMS/Aquidauana, where 7 species of green manures were sown in 5x10 m plots, manually, with the aid of a hoe. Crop management was carried out when necessary, without the application of agrochemicals, only with manual weeding. After flowering, the plants were harvested, and left under the constituent plot. Four samples were weighed per plot of each species, containing 90 g of each material, placed in literbags, produced with 70% shade, with. The samples remained in their respective plots, being collected every 30 days, in 4 evaluation periods. The samples were taken to the laboratory, washed in running water to remove excess soil, dried in an oven at 65ºC until constant weight. Subsequently, the samples were ground in crucibles, and laboratory analyzes were carried out to determine nitrogen (N). Black velvet bean, velvet bean and pork beans had the highest means of N in seasons 0 and 30. For dry mass, velvet bean, velvet bean, pigeon pea, pigeon pea, broad bean and Crotalaria spectabilis had the highest means in the first cutting season.